2021
DOI: 10.1101/2021.04.14.439791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The transcription factor reservoir and chromatin landscape in activated plasmacytoid dendritic cells

Abstract: Transcription factors (TFs) control gene expression by direct binding to regulatory regions of target genes but also by impacting chromatin landscapes and thereby modulating DNA accessibility for other TFs. To date, the global TF reservoir in plasmacytoid dendritic cells (pDCs), a cell type with the unique capacity to produce unmatched amounts of type I interferons, has not been fully characterized. To fill this gap, we have performed a comprehensive analysis in naïve and TLR9-activated pDCs in a time course s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 94 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…performed ATAC‐seq on cells derived and purified from bone marrow. Following preparation of the ATAC‐seq libraries, sequencing and bioinformatics analysis was performed where a genomic signal map was created through simulation, ATAC‐seq peaks were identified and false reads were removed 25 . Hence, the study discovered the pool of TFs and chromatin environment in activated pDCs.…”
Section: Analysis Of Chromatin Accessibility Shows New Features Of Dc...mentioning
confidence: 99%
See 1 more Smart Citation
“…performed ATAC‐seq on cells derived and purified from bone marrow. Following preparation of the ATAC‐seq libraries, sequencing and bioinformatics analysis was performed where a genomic signal map was created through simulation, ATAC‐seq peaks were identified and false reads were removed 25 . Hence, the study discovered the pool of TFs and chromatin environment in activated pDCs.…”
Section: Analysis Of Chromatin Accessibility Shows New Features Of Dc...mentioning
confidence: 99%
“…A study by Mann-Nüttel et al identified several TFs which exhibited binding reactivity with DNA as well as a significant epigenetic modulation. 25 The study identified the entire set of TFs in pDCs which are regulated by TLR9, and the significance of a family of TFs called AP-1 (activator protein 1). In this direction, Mann-Nüttel et al performed ATAC-seq on cells derived and purified from bone marrow.…”
Section: Analysis Of Chromatin Accessibility Shows New Features Of Dc...mentioning
confidence: 99%